Rethinking the Independence of Cuba from Miguel Barnet’s Biography of a Runaway Slave - Fillies Testa Muñoz, Juliana (CIICLA, Universidad de Costa Rica, 2021)
Este documento es una traducción al inglés del artículo original "Repensando la Independencia de Cuba a partir de Biografía de un cimarrón de Miguel Barnet" publicado en este mismo número. The testimonial novel Biography of a Runaway Slave by Miguel Barnet is one of the pioneers of the narrative genre and has attracted the attention of critics from the moment of its publication. Scholars see the testimonial novel as a text that allows the reader access to a "genuine" episteme, safeguarded by a witness of historical events. The main objective of this article is to demonstrate that the narrative of the maroon and former mambí Esteban Montejo opens new ways of reading and analyzing historical events. In particular, I will focus on Montejo’s statements on the Cuban War of Independence. For this purpose, I will use the theory of the Subaltern Studies as a methodological tool. The analysis will show the denial of Afro-Cuban agency in the official history of independence in Cuba, and will offer a reading of the events that recognizes the important Afro-descendant contribution.